Development of RhiNO v2.0: an enhanced single user paddock stand / Wan Muhammad Syahmi Wan Fauzi and Helmi Rashid - Wan Fauzi, Wan Muhammad Syahmi; Rashid, Helmi (Smart Manufacturing Research Institute (SMRI), 2022)
Within the recent past, studies concerning motorcycle have been an enormous area of research interest. Motorcycle nowadays, especially superbike utilized a paddock stand to support the motorcycle in an upright and stable position, which can serve multiple purpose such as washing the motorcycle, tire changing and overall maintenance. In the previous study, there is a development of RhiNO v1.0, a new single user superbike paddock stand that able to overcome the limitation of current paddock stands which require at least two persons for the operation. Although RhiNO v1.0 met its design requirements, there are still room for improvements relating to its size, weight, assembly method and also type of material used for the fabrication. This paper deal with the development of RhiNO v2.0 where the enhancement may overcome the imperfections found from the first prototype without jeopardizing its function. For engineering design and simulation purposes, combination of Computer Aided Design (CAD) and Finite Element Analysis (FEA) through the state-of-art CATIA V5R20 software was extensively used. A prototype based on the design was fabricated and tested as a proof of concept.